Manajemen dan Pengembangan Pendidikan Pondok Pesantren - Adi Sulistyo Wibowo; Muhammad Isa Anshory (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
People have long been aware of the role of trainees because they are able to give birth to reliable cadres who not only have potential but also know how to exploit the potential of their skills. In this global era, the role of science, culture and training must be given greater priority. It has a reputation as a unique Islamic religious institution, especially an educational institution. Nowadays, one of the problems of the training cottage is effective and efficient development management. Therefore, there is a need for a good management and development by a well-experienced and well-informed training hut leader. The internship curriculum is also the most important reviewed entity of academic success. Even though we know that trainees don't have an official government curriculum, it's a policy of every traineeships manager. Therefore, there is a need for the development of the curriculum applied to adapt to current developments. It appears that management and development is a very important strategy for the trainees, namely as the main means of the institution to develop and optimize human resources and curriculum to the desired goals.